Рекурсивная идентификация дискретных динамических систем с одним входом и выходом - Жуков, А.О. (Проблемы управления и информатики, 2009)
Метод рекурсивної (ітеративної) ідентифікації узагальнено для одноканальних дискретних динамічних систем з кратними модами в умовах обмеженої невизначеності. Узагальнення здійснюється на основі модального розкладу відгуку системи з кратними власними числами. Досліджується вплив кратності на точність відновлення порядку та спектра апроксимуючої субмоделі. Показано, що збільшення кратності мод ускладнює розділення корисного сигналу та шуму, а також призводить до розширення інтервалу локалізації власних значень і до редукції визначення кратності мод при ідентифікації систем з великими значеннями кратності в умовах обмеженої невизначеності. The article is devoted to generalization of recursive (iterative) identification method for the single input and single output discrete dynamical systems with multiple modes under bounded uncertainty conditions. Generalization is conducted on the basis of modal decomposition of the system response with the multiple eigenvalues. The influence of multiplicity both on the order recovering precision and on the spectrum of approximating submodel is studied. It is illustrated that increasing of modes multiplicity leads to both difficultes of signal and noise separating and to expanding of eigenvalues localizing interval and to reduction of modes multiplicity determination during systems identification with the high values of multiplicity under bounded uncertainty conditions.